2022
DOI: 10.3389/fgene.2022.982589
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for grain yield and component traits in bread wheat (Triticum aestivum L.)

Abstract: Genomic regions governing days to heading (DH), grain filling duration (GFD), grain number per spike (GNPS), grain weight per spike (GWPS), plant height (PH), and grain yield (GY) were investigated in a set of 280 diverse bread wheat genotypes. The genome-wide association studies (GWAS) panel was genotyped using a 35K Axiom Array and phenotyped in five environments. The GWAS analysis showed a total of 27 Bonferroni-corrected marker-trait associations (MTAs) on 15 chromosomes representing all three wheat subgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 91 publications
2
17
0
Order By: Relevance
“…The highest number of 12 QTLs were identified for PH on the 1B, 2B, 3A, 3B, 3D, 4A, 5A, 5D, 7B, and 7D chromosomes. Plant height is one of the important yield component traits in wheat, and therefore many QTLs were also identified in previous reports on chromosomes 1B [ 10 , 19 , 37 , 40 , 51 ], 2B [ 10 , 40 , 45 , 51 , 53 ], 3A [ 26 , 54 ], 3B [ 10 , 19 , 22 , 40 ], 4A [ 26 , 45 , 52 , 53 ], 5A [ 19 , 26 , 45 , 51 , 53 , 55 , 56 ], and 7B [ 10 ], at different positions. In addition, Alemu et al [ 52 ] identified a QTL on the 4A chromosome at 41cM, which was similar to that of QPH-4A and mapped at 41cM, explaining a 4.58% phenotypic variation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The highest number of 12 QTLs were identified for PH on the 1B, 2B, 3A, 3B, 3D, 4A, 5A, 5D, 7B, and 7D chromosomes. Plant height is one of the important yield component traits in wheat, and therefore many QTLs were also identified in previous reports on chromosomes 1B [ 10 , 19 , 37 , 40 , 51 ], 2B [ 10 , 40 , 45 , 51 , 53 ], 3A [ 26 , 54 ], 3B [ 10 , 19 , 22 , 40 ], 4A [ 26 , 45 , 52 , 53 ], 5A [ 19 , 26 , 45 , 51 , 53 , 55 , 56 ], and 7B [ 10 ], at different positions. In addition, Alemu et al [ 52 ] identified a QTL on the 4A chromosome at 41cM, which was similar to that of QPH-4A and mapped at 41cM, explaining a 4.58% phenotypic variation.…”
Section: Discussionmentioning
confidence: 94%
“…Genome-wide association studies (GWAS) and quantitative-trait-loci (QTL) mapping are the two widely used methods to dissect the genetic basis of complex quantitative traits in crop plants. In previous studies, GWAS panels have been phenotyped in a range of production conditions including drought, irrigated, heat, salt stress, and different nitrogen regimes, to identify QTLs associated with grain yield and its contributing traits through GWAS [ 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Similarly, several QTLs associated with yield and contributing traits have been identified through bi-parental populations-based QTL mapping under diverse production conditions (irrigated, drought, heat, organic) and different genetic backgrounds (synthetic wheat, Rye selections or translocations, non-adapted background) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…MABB is considered as one of the reliable methods to improve a crop variety by incorporating the desired gene(s)/QTLs that govern the trait expression in which the variety is essentially deficient. Numerous reports are available on molecular markers linked with the expression of QTLs for heat-stress tolerance (Devate et al, 2022;Khan et al, 2022;Pinto et al, 2010;Gupta et al, 2012;Gupta et al, 2017) but their use in wheat-breeding programs is still rare. The present study is an attempt of the transfer of QTLs associated with heat stress in to the background of high-yielding wheat varieties using MABB.…”
Section: Discussionmentioning
confidence: 99%
“…High-density SNP markers, which are employed in GWASs, may screen large gene pools of breeding material. GWASa have been widely utilized in numerous crops to predict candidate genes using genome-wide-dense markers for various complex traits ( Sukumaran et al., 2015 ; Liu et al., 2018 ; Srivastava et al., 2020 ; Alseekh et al., 2021 ; Danakumara et al., 2021 ; Devate et al., 2022a ; Khan et al., 2022 ; Tiwari et al., 2022 ). The benefits of GWASs include the ability to identify Marker trait association (MTAs) with high resolution utilizing diverse germplasm, making the method more efficient and less expensive than biparental QTL mapping ( Jin et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%